Revealing the Thermal Safety of Prussian Blue Cathode for Safer Nonaqueous Batteries. Issue 42 (5th October 2021) - Li, Zheng; Dadsetan, Mehran; Gao, Junxian; Zhang, Sensen; Cai, Lirong; Naseri, Ali; Jimenez‐Castaneda, Martha E.; Filley, Timothy; Miller, Jeffrey T.; Thomson, Murray J.; Pol, Vilas G.
Abstract: Prussian blue analogs (PBAs) are promising cathode materials for many next‐generation metal‐ion batteries due to their exceptional electrochemical performance. Their oxygen‐free structure avoids a common battery thermal runaway pathway which requires O2 liberation. Herein, the thermal runaway mechanisms of PBAs are studied from the level of material and full cell in nonaqueous sodium‐ and potassium‐ion batteries (SIBs and KIBs). Their hidden safety issue and a novel runaway mechanism that requires no oxygen evolution are identified. The cyanide groups are released (≈51.4 wt%) as toxic cyanides above 200 °C, which also exothermically react with the electrolyte and cause the runaway. The cyanide gas generation mechanism is proposed as cathode hydrolytic disproportionation by Raman spectroscopy, X‐ray photoelectron spectroscopy, in situ environmental transmission electron microscopy, and operando synchrotron X‐ray diffraction studies. In addition, full‐cell level calorimetric studies reveal mitigated heat generation but lower initiation temperature of runaway from such SIBs and KIBs than conventional LiCoO2 –graphite system. These results change how PBA materials are evaluated from a safety standpoint, suggesting that they cannot be regarded as safe cathodes. They also indicate the correlations between thermal safety and their crystal defects or trapped water content. The proposed thermal runaway mechanism provides insights to assist in the building of safer next‐generation batteries. Abstract : Prussian blue analog (PBA) cathodes are revealed to be thermally unsafe for sodium‐ and potassium‐ion batteries despite their oxygen‐free structure. The proposed mechanism suggests that toxic cyanide gases are liberated at high temperatures, which gives rise to battery thermal runaway by reacting with the electrolyte. Mechanistic determination studies provide strategies to improve the overall thermal safety of PBA‐based batteries.